Optimalisasi Kepemimpinan Camat Untuk Meningkatkan Kinerja Pegawai Dalam Meningkatkan Pelayanan Publik Di Kecamatan (Studi Kasus Kantor Camat Kinali Kabupaten Pasaman Barat Sumatera Barat) - Putra, Michael Ade; Panjaitan, Maringan; Tobing, Artha Lumban (Research and Community Service UNIVERSITAS KALBIS, 2025)
Sub-district leadership plays a crucial role in improving employee performance to improve the quality of public services at the sub-district level. This study aims to analyze the strategy for optimizing sub-district leadership in improving employee performance at the Kinali Sub-district Office, West Pasaman Regency, West Sumatra. The method used in this study is a qualitative approach with data collection through interviews, observations, and documentation studies. The results of the study indicate that optimizing sub-district leadership is carried out through increasing supervision, providing motivation, and strengthening coordination between employees and the community. Factors that support leadership optimization include clear administrative authority and adequate resource support, while the main obstacles faced are lack of employee discipline and limited access to relevant training. The conclusion of this study confirms that effective sub-district leadership contributes significantly to improving employee performance and the quality of public services. Recommendations proposed include improving the performance evaluation system, technology-based employee training, and strengthening transparency in the public service process.